Utilisation of indigenous resources for acoustical applications / Valliyappan D. Natarajan and Mohd Jailani Mohd Nor - Natarajan, Valliyappan David; Mohd Nor, Mohd Jailani (UPENA, 2004)
This paper presents the development of novel sound absorbing materials based on natural indigenous resources particularly that of fibrous nature. Coir fiber in the form of stitched mat, which is porous and fuzzy, was utilized as the main sound absorbing component. Composite panels support the coir mat laterally. The panels were made from oil palm frond fibre (OPF) and rice husk (RH) bounded in either unsaturated polyester (UP) or polypropylene (PP) matrix. The acoustical properties of the composite structures were determined in an impedance tube based on the two-microphone transfer function method in the frequency range of 125Hz to 4000Hz. Overall results indicate that the coir mat-composite panel structure is a potential absorbent-barrier with not less than 50% of sound absorption. General improvements were achieved in the absorption properties over the entire frequency range using the more flexible RH-PP panel while superior low frequency absorption was attained using panel made of 50% volume fraction of OPF I RH mixture in UP. The product of this research offers exceptional cost-performance balance to the existing, relatively expensive noise control industry while reducing waste disposal problems in the plantation industry.